Sanskryckie inskrypcje – niedoceniony rozdział historii klasycznejliteratury indyjskiej - Sudyka, Lidia (Gajt Wydawnictwo 1991 s.c., 2018)
There can be no doubts that the knowledge about precolonial Indian past relies heavily on inscriptional sources. Without epigraphic texts we would hardly know the chronology, or different forms of social, political and economic life. However, after so many years of studying the inscriptions, the fact that some of them need attention simply because they belong to the realm of poetry is still almost overlooked. Inscriptional poetry was completely neglected by Sanskrit theoreticians of literature. The Western as well as Indian modern scholarship in fact seems to share this attitude, although a certain change has been noticed at the end of the 20th century. The presents paper not only aims at presenting indisputable literary merits of the selected specimens but tries to find the reasons why the voice of creators of public poetry was silenced and has no proper place in history of Sanskrit classical literature.
Keywords: Vatsabhaṭṭi; Devagaṇa